Lasso Peptides: Heterologous Production and Potential Medical Application - Cheng, Cheng; Hua, Zi-Chun (Frontiers in Bioengineering and Biotechnology, 2020)
Lasso peptides are natural products found in bacteria. They belong to a specific family of ribosomally-synthesized and posttranslationally-modified peptides with an unusual lasso structure. Lasso peptides possess remarkable thermal and proteolytic stability and various biological activities, such as antimicrobial activity, enzyme inhibition, receptor blocking, anticancer properties and HIV antagonism. They have promising potential therapeutic effects on gastrointestinal diseases, tuberculosis, Alzheimer’s disease, cardiovascular disease, fungal infections and cancer. Lasso peptides with high stability have been shown to be good carriers for other bioactive peptides. These make them attractive candidates for pharmaceutical research. This review aimed to describe the strategies used for the heterologous production of lasso peptides. Also, it indicated their therapeutical potential and their capacity to use as an efficient scaffold for epitope grafting.